THE EFFECT OF ROLE PLAYING LEARNING MODEL ON IMPROVING STUDENT CONCEPT UNDERSTANDING ON ENVIRONMENTAL POLLUTION MATERIAL - Jhon Riswanda; Indah Wigati; Erie Agusta; Teguh Kusuma (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study aims to determine the effect of Role Playing learning model on the understanding of concepts on environmental pollution material . This research was conducted in one of senior high school in Palembang on May 2017. Research method that used in this research is Quasi Experimental with research design of Non - equivalent Control Group Design . The population in this study consists of 4 classes totaling 101 students. Sampling is using purposive sampling technique . The sample of this study X.1 class as the experiment amounted to 26 students and X.2 class as the control class amounted to 24 students. In the learning process, experimental class is taught by using Role Playing learning model and control class is taught by discussion method. Data retrieval is using conceptualization test with essay form that has been tested for its validity and reliability. The results showed that the N-gain average experimental class is 0,71 are categorized as high and N-gain average for the control class 0, 50 including the medium category. Data analysis that is using t-test with significant level 0,05 obtained sig 0,000 <0,05 with t arithmetic = 5.638 while t table = 1.677 seen that t arithmetic > t table . Therefore (H a ) is accepted and (H 0 ) is rejected . Based on this, it can be concluded that there is a significant influence on the model of learning Role Playing on the mastery of the concept of human circulatory system for X class. Keywords: concept mastering, circulatory system, learning model, role playing